Respuesta :

Answer:

1. = 3xy + x - 2y - 4

2. = d^2(2c^3-8c^2d+3d^2)

Step-by-step explanation:

= 9x^2y^2 + 3x^2y - 6xy^2 - 12xy/3xy

First factor the top equation ….

= 3xy(3xy + x - 2y - 4)/3xy

If the top and the bottom both carry 3xy, you can cancel out both of them leaving you with ….

= 3xy + x - 2y - 4

= -16c^6d^6 + 64c^5d^7 - 24c^3d^8/-8c^3d^4

First factor the top equation ....

= -8c^3d^6(2c^3-8c^2d+3d^2)/-8c^3d^4

If the top and the bottom both carry -8c^3 you can cancel out both of them leaving you with ….

= d^6(2c^3-8c^2d+3d^2)/d^4

Apply the exponent rule with d^6 ....

= d^4d^2(2c^3-8c^2d+3d^2)/d^4

cancel out d^4 ....

= d^2(2c^3-8c^2d+3d^2)